2002
DOI: 10.1210/jc.87.7.3475
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Controls Proliferation Versus Differentiation in Human Pancreatic Endocrine Cells

Abstract: Using immortalized human pancreatic endocrine cell lines, we have shown previously that differentiation into hormone-expressing cells requires cell-cell contact acting in synergy with the homeodomain transcription factor pancreatic duodenal homeobox-1 (PDX-1). Although differentiation is associated with a decrease in cell proliferation, the mechanisms behind this relationship are not known. Using TRM-6, a delta cell line, and betalox5, a beta-cell line, we show here that cell-cell contact and subsequent endocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The overall effect of the absence of Aqp7 was a reduction in TUNEL positivity in the pancreatic islets. The reduction in caspase 3 and Bax is consistent with this effect and also with the known stimulatory effect of c-myc overexpression (7,30). The simultaneous fall in the levels of Bcl2 and Bcl-XL, the antiapoptotic transcripts, could be a compensatory change in response to the reduction in apoptotic gene expression.…”
Section: Proliferation-and Apoptosis-related Gene Expression In Isletsupporting
confidence: 80%
“…The overall effect of the absence of Aqp7 was a reduction in TUNEL positivity in the pancreatic islets. The reduction in caspase 3 and Bax is consistent with this effect and also with the known stimulatory effect of c-myc overexpression (7,30). The simultaneous fall in the levels of Bcl2 and Bcl-XL, the antiapoptotic transcripts, could be a compensatory change in response to the reduction in apoptotic gene expression.…”
Section: Proliferation-and Apoptosis-related Gene Expression In Isletsupporting
confidence: 80%
“…[28][29][30][31][32][33] bHLH proteins form obligate homodimers or heterodimers, which bind to regulatory E-box sequences in the ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Id3 Upregulates Brdu Incorporation Associated With a Dna Dammentioning
confidence: 99%
“…Since many differences exist between rodent and human β cells, attempts have been made to generate human β cell lines from many human pancreatic sources, such as adult islets, fetal pancreases, or insulinomas. However, insulin production by these cells was extremely low or these cells were capable of producing insulin only over a few passages (10)(11)(12)(13). In 2005, Narushima et al (14) reported that they successfully established a functional human β cell line, NAKT-15.…”
Section: Introductionmentioning
confidence: 99%